Preventive approaches to the analysis of the adverse impact of production factors in the petrochemical industry on the prevalence of diseases of the cardiovascular system and prevention of man-made emergencies - N. V. Semenova; A. S. Vyaltsin; S. V. Vyaltsin (Лечащий Врач)
Objective. Currently, in Russia, as well as all over the world, an increase in morbidity and mortality from pathologies of the cardiovascular system is registered. Employees of petrochemical production are exposed to a large number of additional factors of the production environment, which in turn increases the cardiovascular risk in this cohort of the population. Petrochemistry is also one of the main industries of great economic and social importance for our country, which makes the study of this problem more relevant.Results. According to the results of many studies, the most common cardiovascular pathology in the studied population is arterial hypertension. Many researchers associate the high prevalence of this nosology not only with the direct influence of production factors, but also with the number of years worked at petrochemical enterprises. The main production factors contributing to the development of circulatory system diseases in petrochemicals employees were identified, for example, noise, exposure to chemical harmful substances, increased stress levels and tension during the work process. These factors act on the worker's body constantly and contribute to an increased risk of developing cardiovascular diseases. The main aspects of the pathological influence of production factors on the health of the workers' organism are analyzed. With the help of the obtained data, ways to solve the problem under study were proposed. The presented materials will help to develop measures for the prevention of the development of diseases of the circulatory system in more detail and narrowly, taking into account the influence of not only the main known risk factors, but additional impacts during the labor process.Conclusion. The proposed measures should be aimed at modifying and improving existing preventive and hygienic measures, as well as contribute to improving the health of petrochemical production workers and reducing the incidence of these nosologies, which in turn will prolong the working capacity of employees and reduce economic losses in production.